2022
DOI: 10.31234/osf.io/r8nyu
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Adjusting for Publication Bias Reveals That Evidence for and Size of Construal Level Theory Effects is Substantially Overestimated

Abstract: Construal Level Theory (CLT) is one of the most foundational theories in social cognition. However, the few replication studies available indicate a mixed pattern regarding the evidence supporting this theory. This article assesses the credibility of CLT more widely by using publication bias correction techniques on published studies in the CLT literature. First, we reanalyse the largest and most recent meta-analysis on CLT using a `RoBMA (robust Bayesian meta-analysis) multiverse' approach with 12 different m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 60 publications
3
17
0
Order By: Relevance
“…Our results and conclusions are in close agreement with recent meta-analytic studies which have shown that after accounting for publication bias, the evidence in favor of CLT is rather weak (Maier et al, 2022). They also align with the recent call for a multi-lab replication project aimed at replicating key experimental findings underlying CLT (https://climr.org/).…”
Section: Clt and Risky Decision-makingsupporting
confidence: 92%
“…Our results and conclusions are in close agreement with recent meta-analytic studies which have shown that after accounting for publication bias, the evidence in favor of CLT is rather weak (Maier et al, 2022). They also align with the recent call for a multi-lab replication project aimed at replicating key experimental findings underlying CLT (https://climr.org/).…”
Section: Clt and Risky Decision-makingsupporting
confidence: 92%
“…Relatedly, it is also possible, despite this being one of CLTs fundamental assumptions, that construal levels do not influence levels of abstraction. Maier et al (2022) used novel bias correction methods to reanalyze the data underlying the largest meta-analysis on CLT (Soderberg et al, 2014). Using a robust Bayesian meta-analysis (Maier et al, 2020), they found evidence against an effect of construal level on abstraction.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the evidence for Construal Level Theory, which underpins the concept of psychological distance, has been found to suffer from publication bias and inconsistent effects (Keller et al, 2022;Maier et al, 2022).…”
Section: Location Of Climate Change Impactsmentioning
confidence: 99%